STUDENTS’ REFLECTION ON MIND MAPPING: A STRATEGY FOR TEACHING READING COMPREHENSION - Iis Suryani Herdiah; Alviaderi Novianti; Diajeng Pritama (JELA (Journal of English Language Teaching, Literature and Applied Linguistics), 2022)
Reading skill needs to be possessed by students. The students should know exactly what they are reading and find the meaning of the text. One of strategies for teaching reading is Mind Mapping technique. This technique of teaching reading is popularly known by the teachers. However, the students’ reflection regarding Mind Mapping is rarely explored. This study discusses what students’ reflection on the use of Mind Mapping in reading comprehension of recount texts. The aim of this study is to find out students' reflection on reading comprehension using Mind Mapping which was applied in English class. This study used case study research involving five students from a vocational high school as participants. Data were obtained from learning logs and semi-structured interviews. The results of research revealed that mind mapping provided many benefits for students. They can answer the reading comprehension questions, understand the content of the story, enhance vocabulary, interesting methods, and enable them to get detailed information. Students agreed that mind mapping should be applied in the learning process in the future, especially in reading class.